22. Multicentric test-retest reproducibility of human hippocampal volumes with FreeSurfer 6.0: A comparison between standard and longitudinal hippocampal subfields segmentation streams applied to 3D T1, 3D FLAIR and high-resolution 2D T2 neuroimaging. (December 2018) - Chiappiniello, A.; Tarducci, R.; Muscio, C.; Frisoni, G.B.; Bruzzone, M.G.; Bozzali, M.; Perani, D.; Tiraboschi, P.; Nigri, A.; Ambrosi, C.; Caulo, M.; Chipi, E.; et al.
Abstract : Introduction: The Italian AD-NET project is a multicentric initiative focused on the early recognition of Alzheimer's Disease integrating clinical, imaging, and molecular data. This preliminary study reports test-retest reproducibility of hippocampus and its subfields segmentation, using the FreeSurfer 6.0 longitudinal processing with FLAIR alone and together with high-resolution T2. Materials and Methods: Six clinical MRI sites across Italy currently participate in the project. The acquisition protocol included a 3D sagittal T1 both at the beginning and at the end of the scanning session, a 3D axial FLAIR and a high-resolution coronal T2. Each site recruited 5 healthy volunteers who were scanned in two different sessions a week apart. The preliminary results presented in this study are referred to 12 subjects. The images were processed according to the longitudinal stream of FreeSurfer 6.0. A within-session T1 averaging was performed to improve the reproducibility and FLAIR images were used in PIAL surface reconstruction. Then both standard hippocampal subfields segmentation (SHS) stream using the high-resolution T2 and longitudinal hippocampal subfields (LHS) stream were executed. The test-retest reproducibility error (RE) of the segmented volumes was calculated as the absolute volume differences across sessions relative to their mean. For each volume, the average RE value across subjects was calculated. Results: The average RE related to the LHS stream ( ≈ 2%) is lower than using the SHS stream ( ≈ 3%). As shown in figure, the reproducibility with the LHS stream is higher for any volume except for the hippocampal fissure (Hp_ fiss). Irrespective of the stream used, the findings are generally better than those of other published studies, where no FLAIR and high-resolution T2 images were used. Conclusions: Preliminary results of this study suggest high volume reproducibility for the different hippocampal subfields and the whole hippocampus. Moreover, the LHS stream showed a better reproducibility compared to the SHS stream. Acknowledgments: This study was supported by the Italian Minister of Health, grant number: NET-2011-02346784.